Relationship between Remaining Teeth and Arterial Stiffness in Elderly Patients - Kim, Barkhwa; Oka, Synichi; Takada, Koji (Ronen Shika Igaku, 2006)
Periodontal disease increases the risk of cardiac diseases, leading us to suppose that oral health affects the general condition. However, there are few reports where the general condition was evaluated with a simple objective method for comparative examination with the oral cavity. On the other hand, it has been clarified both that arteriosclerosis progresses prior to the onset of cardiac disease and also that sclerosis of the aorta precedes sclerosis of the cerebroartery or coronary artery. Thus, in the present study we retrospectively examined the relationship between the remaining teeth and arterial stiffness to find out correlations of the oral cavity with the general condition. This was achieved by interpreting the arterial stiffness as an indicator of the general condition. The subjects were 140 oral surgery patients (male: female=83: 57, 61.3±9.0 years old, Body Mass Index 23.2±3.4 [mean±SD]) without a history of cerebrovascular disorder and heart disease. They were subjected to digital panoramic radiography and a clinical examination. To evaluate the oral cavity, we examined the number of remaining teeth on the panoramic radiograph and the ratio of the number of the teeth with a crown-root ratio of higher than 1: 1 on alveolar osteoid images, to the number of remaining teeth. Brachial-ankle pulse wave velocity (baPWV) and cardio-ankle vascular index (CAVI) were used as indices of arterial stiffness. With each of these parameters, higher values indicate stiffer vascular walls. The following were revealed by examining correlations between the dental condition and the arterial stiffness parameters: 1) The number of remaining teeth was negatively correlated with both baPWV and CAVI; the lower the number of remaining teeth, the higher the baPWV (r=-0.29, P=0.0003) and CAVI (r=-0.33, P<0.0001). 2) The ratio of the number of teeth with a crown-root ratio of higher than 1: 1 to the number of remaining teeth positively correlated with both baPWV and CAVI ; the higher the rate of alveolar bone resorption, the higher the baPWV (r=0.22, P=0.0106) and CAVI (r=0.31, P=0.0002). Thus, both the number of remaining teeth and the status of alveolar bone resorption correlated with baPWV and CAVI, suggesting that a reduced number of remaining teeth or the progress of alveolar bone resorption increases arterial stiffness.